Sistematization of perioperative care - a qualitative research - Grittem, Luciana; Meier, Marineli Joaquim; Peres, Aida Maris (Online Brazilian Journal of Nursing, 2009)
Qualitative study which objectified to develop a cooperative process in order to structure perioperative nursing at the surgical unit of a hospital in Curitiba/Brazil. Action-research was the methodology used with seven nurses from the surgical unit. The following thematic categories emerged: organizational structure hindering nurses’ decision-making; basic conditions for perioperative nursing care; caring/managerial nursing work process in the surgical unit; caring/managerial nursing attributions in the surgical unit; perioperative nursing instrument; inclusion of nursing diagnosis in the perioperative nursing instrument; relevant information for the transoperative phase; immediate post-operative period as the action setting for perioperative nursing. The discussion process enabled the reflection on perioperative nurses’ professional practice as well as their actions towards professional recognition.